Influence of Al(III) on biofilm and its extracellular polymeric substances in sequencing batch biofilm reactors. Issue 1 (2nd January 2019) - Hu, Xuewei; Yang, Lei; Lai, Xinke; Yao, Qi; Chen, Kai
ABSTRACT: This paper presented the influence of Al(III) on biodegradability, micromorphology, composition and functional groups characteristics of the biofilm extracellular polymeric substances (EPS) during different growth phases. The sequencing batch biofilm reactors were developed to cultivate biofilms under different Al(III) dosages. The results elucidated that Al(III) affected biofilm development adversely at the beginning of biofilm growth, but promoted the biofilm mass and improved the biofilm activity with the growth of the biofilm. The micromorphological observation indicated that Al(III) led to a reduction of the ﬁlaments and promotion of the EPS secretion in growth phases of the biofilm, also Al(III) could promote microorganisms to form larger colonies for mature biofilm. Then, the analysis of EPS contents and components suggested that Al(III) could increase the protein (PN) of tightly bound EPS (TB-EPS) which alleviated the metal toxicity inhibition on the biofilm during the initial phases of biofilm growth. The biofilm could gradually adapt to the inhibition caused by Al(III) at the biofilm maturation moment. Finally, through the Fourier transform infrared spectroscopy, it was found that Al(III) was beneficial for the proliferation and secretion of TB-EPS functional groups, especially the functional groups of protein and polysaccharides.